Links between animal welfare and “One Health”: perception and implementation in Latin America - Racciatti, Débora Silvia; Wiemeyer, Guillermo María; González Gracia, Luis Andrés; Blanco, Carlos; Szmelc, Andrea; Orozco, María Marcela (Frontiers in Animal Science, 2023)
The recent COVID-19 pandemic has highlighted the crucial role of the "One Health" (OH) concept in the prevention, early detection, and mitigation of health issues involving humans, animals, and the environment. Recognizing the intrinsic interdependence among human health, animal health, and environmental well-being is crucial, demanding heightened emphasis. Many health challenges stem from situations that compromise animal welfare (AW), human well-being, environmental sustainability, and vice versa. Recognizing the significance of AW across its five domains is essential for preventing future pandemics and advancing global objectives such as food security, reduction of human suffering, biodiversity conservation, and enhanced productivity in the agricultural-livestock sector. From March to May 2023, we conducted an online survey using QuestionPro® to explore perceptions, experiences, ongoing strategies, and activities within disciplines linked to AW and the OH approach in Latin America. Respondents included stakeholders from various disciplines associated with OH and AW. Our findings reveal that both concepts are currently undergoing an expansion phase in Latin America. However, the interdependencies between AW and OH are not widely recognized. While animal welfare frequently receives significant attention from diverse educational perspectives, the OH approach has gained considerable momentum over the past decade. Academic sectors and non-governmental organizations (NGOs) are driving initiatives bridging AW and OH in Latin America, underscoring the need for robust public policies to ensure sustainable strategies. Advocating for greater awareness of the interdependence between AW and OH, this study highlights knowledge gaps among the scientific community and policymakers. Actively engaging with these connections can foster comprehensive strategies to address global health challenges and enhance overall well-being. The "One Welfare Framework" and other integrative frameworks hold promise in strengthening the linkages between AW and OH, facilitating theory translation into practical action. Establishing comprehensive, integrated policies that unite these domains is imperative for addressing complex health challenges and advancing the welfare of both animals and humans. Further research and collaborative efforts are essential to transform these concepts into tangible, impactful outcomes.